Inside Windows 98 - Boyce, Jim, 1958- (Indianapolis, Ind. : New Riders Pub., 1998)
A reference and tutorial to Windows technologies, this work is intenteded for intermediate and experienced Windows users and administrators. It provides a reference to such areas as Windows technology, memory management, optimization, using workgroup applications, data sharing and multimedia
Overview and setup; working with Windows 98; Windows 98 architecture and optimization; putting Windows 98 to work; integration and automation; messaging and communications; sharing resources and using the Internet; BackOffice integration.
Includes index.
Keywords: Microsoft Windows (Computer file); Operating systems (Computers)